An ionized superbubble powered by a protocluster at z = 6.5. (18th March 2020) - Rodríguez Espinosa, J M; Mas-Hesse, J M; Salvador-Solé, E; Calvi, R; Manrique, A; Chanchaiworawit, K; Guzman, R; Gallego, J; Herrero, A; Marín Franch, A
ABSTRACT: We show herein that a proto-cluster of Ly α emitting galaxies, spectroscopically confirmed at redshift 6.5, produces a remarkable number of ionizing continuum photons. We start from the Ly α fluxes measured in the spectra of the sources detected spectroscopically. From these fluxes, we derive the ionizing emissivity of continuum photons of the protocluster, which we compare with the ionizing emissivity required to reionize the protocluster volume. We find that the sources in the protocluster are capable of ionizing a large bubble, indeed larger than the volume occupied by the protocluster. For various calculations, we have used the model AMIGA, in particular to derive the emissivity of the Lyman continuum photons required to maintain the observed volume ionized. Besides, we have assumed the ionizing photons escape fraction given by AMIGA at this redshift.